Design of electrical system of the simulation center for Hamad Bin Khalifa Medical City Doha, State of Qatar - Estebal, Edgardo E. (Manila Professional Regulation Commission, 2015)
The Hamad Medical City Simulation Center is a state of the art education and simulation located on the campus of Hamad Bin Khalifa Medical City, Doha, State of Qatar. The center will accommodate education and training for HMC professional staff, newly hired clinical and nursing staff and medical resident. It will also provide auditorium and lecture space for the larger medical community. The building power distribution system was designed with a local standby low voltage emergency diesel generator sets, 415V, class G3 with associated automatic transfer switch. This generator will supply electrical power to critical and essential loads systems. Uninterruptible power supply (UPS) system are provided to maintain continuous power for the security, data/communication system and BMS/SCADA systems that need to be operational at all times. The building will be powered by a Dry type transformer rated 1600kVA, 11/0,433kV, 3 Phase, 50Hz and connected to the indoor LV networks which comprise the Main distributions boards (MDBs) located at MDB room, distribution panels (DPs & EDPs), final branch circuit panelboards (DBs & EDBs) located at the electrical rooms and motor control centers/panels (MCCs/MCPs) located at the Mechanical rooms. The low voltage (LV) cable distribution networks was designed to ensure that the voltage drop from the transformer up to the farthest end of a branch circuit will not exceed the five percent (5%) requirement. Fire pump is not discussed in this report, as the whole complex has been designed with a centralized fire pump located in HBKMC Central Energy Plant building.
Technical report submitted in partial fulfillment of the requirements for the licensure examinations for professional electrical engineers.
E2-677G donated by Mr. Jaime V. Mendoza.
Keywords: Buildings -- Electric equipment